Inhibitory Effects of Betulinic Acid on LPS-Induced Neuroinflammation Involve M2 Microglial Polarization via CaMKKβ-Dependent AMPK Activation - Li, Chuwen; Zhang, Chao; Zhou, Hefeng; Feng, Yu; Tang, Fan; Hoi, Maggie P. M.; He, Chengwei; Ma, Dan; Zhao, Chao; Lee, Simon M. Y. (Frontiers in Molecular Neuroscience, 2018)
Scope: In response to the microenvironment, microglia may polarize into either an M1 pro-inflammatory phenotype, exacerbating neurotoxicity, or an M2 anti-inflammatory phenotype, conferring neuroprotection. Betulinic acid (BA) is a naturally pentacyclic triterpenoid with considerable anti-inflammatory properties. Here, we aim to investigate the potential effects of BA on microglial phenotype polarization and to reveal the underlying mechanisms of action. Firstly, we confirmed that BA promoted M2 polarization and inhibited M1 polarization in LPS-stimulated BV-2 microglial cells. Then, we demonstrated that the effect of BA on microglial polarization was dependent on AMP-activated protein kinase (AMPK) activation, as evidenced by the fact that both AMPK inhibitor compound C and AMPK siRNA abolished the M2 polarization promoted by BA. Moreover, we found that calmodulin-dependent protein kinase kinase β (CaMKKβ), but not liver kinase B1 (LKB1), was the upstream kinase required for BA-mediated AMPK activation and microglial M2 polarization, via use of both the CaMKKβ inhibitor STO-609 and CaMKKβ siRNA. Finally, BA enhanced AMPK phosphorylation and promoted M2 microglial polarization in the cerebral cortex of LPS-injected mice brains, which was attenuated by pre-administration of AMPK inhibitor. This study demonstrated that BA promoted M2 polarization of microglia, thus conferring anti-neuroinflammatory effects via CaMKKβ-dependent AMPK activation.